A Discourse Analysis of American Folktale âthe Monkeyâs Pawâ - Syam, Andi Tenrisanna (Ahmad Dahlan Journal of English Studies, 2017)
Discourse analysis studies language in use taking into account important elements such as coherence (unity of the text) and cohesion (tools that tie together sentences, e.g. pronouns). American folktale âthe monkeyâs pawâ is written by W.W. Jacobs. "The Monkeyâs Paw". It is clearly illustrates the old adage, "Be careful what you wish." It presents the usual Mr. White with magical items and allows his characters (curiosity, the desire to be free of debt) to destroy him. The monkeyâs paw permits his wishes, but never the way he imagined. In his time, Jacobs was primarily known as a novelist of some funny novel. Sense of humour disclosure "The Monkeyâs Paw," which is the use of what is now called black humour. The data sources of this paper were the written materials. Written materials mean that the data of this paper taken from a folktale written in English. The items were analyzed namely: (1) cohesion and deixis; (2) cohesive devices; (3) substitution; (4) ellipsis; (5) conjunction, and (6) lexical ties.